Molecular and Biochemical Study for (VDBP) gene in women Suffered with osteoporosis in Mosul City - Samaa M. AL. Sael; Owayes M. Hamed (African Journal of Advanced Pure and Applied Sciences, 2022)
An The GC gene encodes the protein VDBP, which plays an important role in the transport of vitamin D. This protein belongs to the albumin family. The GC gene is located on the long arm of chromosome 4 (4q12-q13), which consists of 1690 nucleotides, and the GC gene has many genetic variations that are related to variation Single nucleotide SNPs and the proteins resulting from these variations differ in their ability to bind with VD and its different forms. due to the presence of two genetic variations, rs7041 and rs4588 for VDBP, three phenotypes were identified which are Gc1s, Gc1f and Gc2, which differ in their ability to bind to the inactive form of vitamin D 25(OH)D3. It has been proven that the variants in this gene change the concentrations of OH-D325 in the plasma, so the defect in these variants of the VDBP gene is closely related to many diseases, including VD deficiency and cancer. The current study included (96) women with ages ranging between (45-35) years who were referred to the private pathological analysis laboratories in the city of Mosul in a period of time that ranged from September to November of 2021. The samples were divided into two groups, the first included 25 women who returned as a control group. The second included 71 women with VD deficiency. The concentration of vitamin D (OH) D325 in the serum is widely used to determine the deficiency in the level of VDBP.